1993
DOI: 10.1093/rheumatology/32.11.1012
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluating the Need for Hospitalization Following Synovectomy Using Yttrium-90 Silicate

Abstract: In 51 patients treated with Yttrium-90 (Y-90) synovectomy for rheumatoid (inflammatory) arthritis (IA) and OA of the knee we found that decreased retained knee activity (RKA) and increased extra-articular activity in lymph nodes and liver are more likely to be found in IA than OA and following bilateral knee injections. Joint inflammation, as assessed by radionuclide blood pool scan but not by SF white cell count, correlates with decreased RKA and increased activity in lymph nodes. Intra-articular steroid had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…This result coresponds with other reported observations, mainly in patients with arthritis. 15,16,21,22 Blood-pool activity is supposed to represent acute synovitis, which is the main target of radiosynovectomy. Nuss et al reported that the severity of synovial hyperplasia was generally unchanged 6 months after radiosynovectomy despite an improvement in hemorrhage frequency based on MRI findings in patients with hemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…This result coresponds with other reported observations, mainly in patients with arthritis. 15,16,21,22 Blood-pool activity is supposed to represent acute synovitis, which is the main target of radiosynovectomy. Nuss et al reported that the severity of synovial hyperplasia was generally unchanged 6 months after radiosynovectomy despite an improvement in hemorrhage frequency based on MRI findings in patients with hemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…3 The relatively long half life of 90 Y (2.7 days) is an argument for post-injection immobilisation (usually 72 h) to minimise extra-articular leakage to the bloodstream by intermittent intra-articular pressure in the ambulant patient and as such improve retention in the knee. 4 The clinical outcome of RSO has been suggested to depend on the primary disease and pre-existing radiological damage. 5 Previous studies also indicated that the efficacy might depend on the diagnosis: patients with rheumatoid arthritis might respond better to RSO than those with other arthritides caused by a more pronounced synovial tissue proliferation in rheumatoid arthritis.…”
mentioning
confidence: 99%
“…Necrosis of the synovium, followed by fibrosis and, finally, sclerosis, is induced by local irradiation. The half‐life of 90 Y is 2.7 days, and for this reason, the injected extremity is immobilized for 72 hours to minimize extraarticular leakage into the bloodstream that typically occurs through intermittent IA pressure in the nonimmobilized extremity (3). Immobilization itself may also lead to a reduction in synovitis (4–9).…”
mentioning
confidence: 99%